Bridging the Gap Between Design and Practice: The Implementation of SILOG in Election Logistics - Matheus Gratiano Mali; Faisal Yudi Anugerah; Eko Ari Wibowo (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2026)
The rapid development of information and communication technology has encouraged governments to adopt digital systems to improve the efficiency, transparency, and accountability of public services. One form of this transformation is the implementation of E-Government in election administration, including the use of the Logistics Information System (SILOG) by the General Election Commission (KPU). Logistic Information System is a technology-based system designed to integrate the planning, management, distribution, and monitoring of election logistics in a digital and integrated manner. The implementation of this system is important to support more effective, accurate, and well-documented election logistics management. This study aims to analyze the implementation of SILOG in election logistics management at the KPU of Magelang City. The research employs a descriptive qualitative approach with data collected through in-depth interviews, observations, and documentation studies. Informants were selected using purposive sampling and snowball sampling techniques involving several parties directly involved in managing the system. The analysis applies an E-Government framework that includes aspects of support, capacity, value, willingness, and local culture, as well as the identification of supporting and constraining factors in its implementation. The findings indicate that the implementation of SILOG contributes to supporting a more integrated and digital-based election logistics management process. Its implementation is influenced by various factors related to institutional support, resource capacity, and technical and organizational conditions in practice